PEMBERIAN TERAPI BEKAM TERHADAP PENURUNAN TINGKAT DEPRESI PASCA GEMPA PADA WANITA DI DESA PASIR PUTIH - Harlina Putri Rusiana; Rias Pratiwi Safitri; Fitri Romadonika; Baiq Nurul Hidayati; Nurwahida Sarma Ningsih (Stikes Yarsi Mataram, 2022)
Earthquake disasters can cause tremendous impacts on all aspects of the lives ofdisaster victims, both physical, social and psychological aspects. Earthquakevictims not only experience emergency problems such as physical damage dueto the earthquake, but also mental and psychological health problems, such as:anxiety (anxiety), stress (pressure), depression (mood), and trauma. Depressioncan have a variety of adverse effects on body health. Starting from sleepdisorders (insomnia and hypersomnia), social relationships or interactions, work,eating patterns, destructive behaviors, even suicide. So that it requires therapythat can reduce the condition of depression through the Prophet's treatmenttherapy, namely: cupping as an alternative to pharmacological treatment. Thisservice activity aims to reduce the level of depression in clients who experiencedepression after the earthquake in Pasir Putih Village.